2017
DOI: 10.1039/c6nr09362k
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-stabilized gold nanoparticles hinder fibrillogenesis of a pathological variant of β2-microglobulin

Abstract: Nanoparticles have repeatedly been shown to enhance fibril formation when assayed with amyloidogenic proteins. Recently, however, evidence casting some doubt about the generality of this conclusion started to emerge. Therefore, to investigate further the influence of nanoparticles on the fibrillation process, we used a naturally occurring variant of the paradigmatic amyloidogenic protein β-microglobulin (β2m), namely D76N β2m where asparagine replaces aspartate at position 76. This variant is responsible for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 35 publications
(18 reference statements)
4
47
0
Order By: Relevance
“…The fluorescence of W60G variant is, indeed, approximately 20% lower than the value of wild-type protein. This result is consistent with a strong localization of the electrostatic interaction, probably being due to the compactness of the NP electron plasma [14,15]. The character of the interaction surface, as described in Figure 6, can be appreciated when compared to the β2m regions that are involved in the contacts with the heavy chain of type I major histocompatibility complex (MHC-I) [19].…”
Section: Protein-aunp Interactionsupporting
confidence: 77%
See 4 more Smart Citations
“…The fluorescence of W60G variant is, indeed, approximately 20% lower than the value of wild-type protein. This result is consistent with a strong localization of the electrostatic interaction, probably being due to the compactness of the NP electron plasma [14,15]. The character of the interaction surface, as described in Figure 6, can be appreciated when compared to the β2m regions that are involved in the contacts with the heavy chain of type I major histocompatibility complex (MHC-I) [19].…”
Section: Protein-aunp Interactionsupporting
confidence: 77%
“…The interaction of β2m and its variants with AuNPs has been thoroughly investigated by our group [14,15]. We found that the actual interaction between the citrate-coated surface of AuNPs and β2m is essentially of electrostatic nature, although the overall protein charge should be around zero or slightly negative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations